Pengaruh DOL, DFL, CR, Dan TATO, Terhadap EPS Pada Perusahaan Telekomunikasi Yang Tedaftar di BEI Periode 2014-2019 - Lu’luil Maknun Thohirin; Purnamawati Purnamawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The aim of this research is to identify influence of Operating Leverage (DOL), Financial Leverage(DFL), Current Ratio (CR), and Total Asset Turnover (TATO) to Earning Per Share (EPS) on Telecommunication Companies in Indonesia Stock Exchange in the period 2014-2019. This research was conducted descriptive, using quantitative descriptive methods. Data collection techniques were carried out by means of documentation studies and literature studies. The data analysis technique used classical assumption test, and multiple linear regression analysis. The result of this study is indicated 1) Operating Leverage (DOL) has a positive and significant effect on Earning Per Share (EPS); 2) Financial Leverage (DFL) has a negative and significant effect on Earning Per Share (EPS); 3) Current Ratio (CR) has a negative not significant effect on Earning Per Share (EPS); 4)Total Asset Turnover (TATO) has a positive and significant on Earning Per Share(EPS); 5) Operating Leverage (DOL), Financial Leverage (DFL), Current Ratio (CR), and Total Asset turnover (TATO) affect the Earning Per Share (EPS).